Health Education About Clean and Healthy Living Behavior at SDN 2 Kedung Pedaringan Kepanjen, Malang Regency - Nafiisah, Adilah; Ayu Wardani , Aradea Putri; Saidah, Dinda Auliyatus; Liza, Diva Natasya; Syahira , Fahriah Firda; Sa’adah , Galuh Lailatus; Rahma, Hanifa Aulia; Rahman, Ibrahim Khalil; Kania, Kaela Rahma; Eka Restu, Mayravanya Zakiya; Ilmi Al Amin, Moh. Fahimul; Tsurayya , Nabila Hilmi; Nurtiana, Yulia Ayu (Inovasi Lokal, 2023)
Perilaku Hidup Bersih dan Sehat (PHBS) is essential for everyday life and can be implemented invarious settings. Schools, as influential institutions, have a crucial role in shaping students' clean andhealthy living behavior. This study aimed to enhance students' knowledge of PHBS and their willingnessto practice it in school. We conducted a quantitative survey using a One Group Pre-test and Post-testdesign, involving all students from grades 1 to 5 at SD Negeri Kedung Pedaringan 2 in Malang Regency.Observations revealed that some students already practiced certain aspects of PHBS, such ashandwashing and proper waste disposal, albeit without recognizing their connection to a Clean andHealthy Lifestyle. To address this, we provided educational materials, using posters for grades 1-3 andPowerPoint presentations for grades 4 and 5. The engaging materials captured the students' interest, andthey actively participated, including singing about PHBS. Post-tests indicated a significant increase intheir knowledge and enthusiasm for implementing PHBS. In conclusion, PHBS is vital in everyday life,particularly within the school environment. This study emphasized the role of teachers in guidingstudents and fostering strong teacher-student relationships. By promoting PHBS, schools can becomecleaner, healthier, and disease-free environments. Future research should delve deeper into enhancingstudents' understanding and interest in their school's PHBS environment. The hope is that such effortswill continue to improve the cleanliness and health of school environments, ultimately benefitingstudents and the community as a whole.